El derecho al trabajo y la estabilidad laboral en el sector público del cantón Pastaza - Atsamp Mashiant, Kerua Tony (2025)
In this scientific article, an analysis and evaluation of the labor relations between workers and employers through the regulation of the right to work in its different modalities and conditions was made, emphasizing the need to know the regulations and find a strategy to channel the duties and responsibilities of the State towards the citizens. Likewise, emphasis was made on the need to have a deep analysis as a means to channel and have the desired success in the work environment in relation to the provision of public and private services, whether physical or intellectual. The indicators were used and compared to show the dependency reaction and the notorious differences between the different forms of intellectual and physical service provision. The parameters used in the preparation of this critical analysis document make it clear that regulatory reform is necessary to better establish and delimit the essential characteristic of guarantees of rights and social justice, such as equality. Consequently, the environment in which the rights of workers are developed is described, making a journey until it leads to the current reality. The problem is raised, which is the reason for the analysis and development of this document. Finally, in compliance with the general and specific objectives of this research, a proposal to solve the identified problem is highlighted.